2006
DOI: 10.1002/hbm.20211
|View full text |Cite
|
Sign up to set email alerts
|

Common deactivation patterns during working memory and visual attention tasks: An intra‐subject fMRI study at 4 Tesla

Abstract: This parametric functional magnetic resonance imaging (fMRI) study investigates the balance of negative, and positive fMRI signals in the brain. A set of visual attention (VA) and of working memory (WM) tasks with graded levels of difficulty was used to deactivate separate, but overlapping networks that include the frontal, temporal, occipital, and limbic lobes; regions commonly associated with auditory and emotional processing. Brain activation (% signal change, and volume) was larger for VA tasks than for WM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
152
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(179 citation statements)
references
References 46 publications
(71 reference statements)
26
152
1
Order By: Relevance
“…These regions all reside along the midline of the brain and are part of the defaultmode brain circuitry Shulman et al, 1997). The current results are thus consistent with previous studies associating deactivation of this network of brain regions with goal-directed behaviors and/or mental effort during a cognitive task (Greicius et al, 2003;Greicius and Menon, 2004;Raichle et al, 2001;Shulman et al, 1997;Tomasi et al, 2006). These results accord particularly well with the aforementioned study showing that attentional lapses are associated with increased "default-mode" network activity (Weissman et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These regions all reside along the midline of the brain and are part of the defaultmode brain circuitry Shulman et al, 1997). The current results are thus consistent with previous studies associating deactivation of this network of brain regions with goal-directed behaviors and/or mental effort during a cognitive task (Greicius et al, 2003;Greicius and Menon, 2004;Raichle et al, 2001;Shulman et al, 1997;Tomasi et al, 2006). These results accord particularly well with the aforementioned study showing that attentional lapses are associated with increased "default-mode" network activity (Weissman et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, among the brain regions in the default network, the PCC/precuneus appears to play a critical role in determining cognitive performance. On the other hand, the default circuitry is probably involved in a wide range of cognitive functions; while some studies suggested that deactivation of the default brain circuitry appears to be invariant to specific behavioral tasks in which observers are involved Tomasi et al, 2006), other studies have provided evidence for functional specificity, such as the medial prefrontal cortex in self-referential mental activity, the ventral medial prefrontal cortex in mediating physiological arousal, the right insula during stimulus-independent thoughts, and the right temporal parietal junction during visual search Mason et al, 2007;Nagai et al, 2004;Shulman et al, In Press). Further studies are thus warranted to examine how these brain regions are involved differently when we are engaged in varying task conditions and, indeed, in different neurological conditions (Greicius et al, 2004;Greicius et al, In press;Kennedy et al, 2006;Laufs et al, In press;Rombouts et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the definition of the DMN, the above regions are typically deactivated during performance of a WM task in fMRI experiments (Anticevic et al, 2010;Hampson et al, 2006;Tomasi et al, 2006). Due to the complex nature of WM, the pattern of task-related, or activated, regions is rather variable, but it typically includes lateral prefrontal, premotor and lateral posterior parietal cortices (Collette et al, 1999;Owen et al, 2005).…”
Section: Discussionmentioning
confidence: 64%
“…Also in the study of , workload-dependent increases were found over parietal sensors as well as in occipital sensors. In two recent fMRI studies bilateral activation was found in the cuneus during WM tasks (Tomasi et al, 2006;Lagopoulos et al, 2007). In one study, stronger cuneus activation was reported for high-workload conditions (Tomasi et al, 2006).…”
Section: Alpha Increase May Reflect Wm Maintenance or Inhibition Of Tmentioning
confidence: 92%